STRATEGY ANALYSIS “LAGOON AVENUE MALL” TOWARDS SDG 5 TARGET: (Case Study at Lagoon Avenue Mall Sungkono Surabaya) - NDINI, AYU SEKAR; MULYASARI AGUSTINI, PRIMA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This research focuses on analyzing the digital marketing strategy implemented by Lagoon Avenue Mall Sungkono Surabaya to achieve the SDG 5 target, which focuses on women's empowerment. By using a qualitative approach, this research aims to explore and understand in depth the strategies that have been implemented by Lagoon Avenue Mall internal parties in order to increase sustainable development by strengthening the role of women in this context. Primary data for this research was obtained through in-depth interviews with internal parties at Lagoon Avenue Mall Sungkono Surabaya as well as parties from the community or event organizers who had collaborated in organizing events at the mall. By combining internal and external perspectives, this research produces a comprehensive understanding of the digital marketing strategies that have been implemented as well as the challenges faced by Lagoon Avenue Mall in achieving SDG 5 goals. The results of the analysis show that although Lagoon Avenue Mall Sungkono Surabaya has implemented several successful strategies , such as targeting specific market segments and focusing on developing events in malls, there are still several areas that require improvement. For example, a lack of precision in defining target audiences and evaluating campaign performance can reduce the effectiveness of their marketing efforts. Apart from that, less interesting content and low user engagement are also obstacles in achieving marketing goals. Other challenges include administrative issues related to rental contracts, uncertainty about the non-financial benefits of collaboration, and competition with other malls or events in the area. This research provides valuable recommendations for Lagoon Avenue Mall Sungkono Surabaya to improve their digital marketing strategy to support the achievement of SDG 5 targets, especially regarding women's empowerment. By improving existing strategies and overcoming the challenges faced, it is hoped that Lagoon Avenue Mall can be more effective in contributing to sustainable development and achieving the goals set in the SDG agenda.